Conversion to Islam in South Asia: Problems in Analysis (American Journal of Islam and Society, 1989)
From the earliest times, South Asia* has been a scene of invasion. Itis a long tale of incursion. conquest, settlement, and then assimilation. TheGreeks, Sakas, and Eushanas forced their way in as dominant groups andestablished kingdoms and dynasties, only to be assimilated by what Dr. Spearcalled "the Hindu sponge." The push by Muslims into the sub-continent wasby well-worn routes and to a familiar pattern of conquest and rule, first ofSind and the Punjab, then of the Gangetic Plain, and, finally, of almost thewhole of South Asia.Conquest and settlement were not followed by assimilation, however.Muslims retained a separate identity and their numbers, proportionate andabsolute, grew until today a quarter of all Muslims in the world are to befound in South Asia. In 1975, they formed some 97 percent of the populationof Pakistan, 85 percent of that of Bangladesh, and 13 percent of that ofIndia.But these Muslims come from different roots and origins, they speakdifferent languages, and their understanding and practice of Islam differs accordingto their educational and social background and to their regional andgeographicaJ setting. Many of them are of Arab, Afghan, Mughal and Persiandescent, but the majority of them are descendants of South Asian convertsto Islam.The spread and expansion of Islam and its acceptance by such large groupsof people of a variety of ethnic, historical, and cultural backgrounds andacross a range of diverse geographical areas can scarcely be the outcomeof any simple uniform process. Conversion to Islam is thus a challengingand absorbing subject for research. Yet it has attracted the attention of scholarsonly since the last decade of the nineteenth century.What follows does not claim to be more than a pre! iminary and ratherhurriedly prepared survey of the main theories about conversion to Islampropounded by Asian and Western scholars. The dearth of source materialpresents difficulties as "medieval Islam" produced no missionaries, bishops,baptismal rites, or other indicators of conversion that could be convenientlyrecorded by the Muslim chronicler. Hopefully the subject will be a spurto the detailed review and analysis of sources, modern and medieval, whichthe subject both deserves and requires ...